Relationship between Preoperative Anxiety and Postoperative Pain among Patients undergoing Elective Surgery in Tertiary Care Center - Subedi, Seema; Shrestha, Sanjesh (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: Appropriate postoperative pain management benefits patients by reducing postoperative cognitive impairment, improving quality of life, and lowering the risk of chronic postsurgical pain. The objective of this research was to explore the relation between anxiety before surgery and pain experienced after surgery in patients undergoing elective procedures.Methods: This descriptive cross-sectional study was conducted among patients undergoing elective surgery. Data were collected via self-administered standard semi-structured questionnaires (Amsterdam Preoperative Anxiety and Numerical Pain Rating scale). Descriptive statistics including frequency, percentage, and mean were used for data analysis. Chi-square test and logistic regression were performed to identify associations between preoperative anxiety and socio demographic variables.Results: Out of 109 respondents, 86(78.90%) had preoperative anxiety. There was a significant correlation between preoperative anxiety and the level of postoperative pain experienced two hours after surgery. Similarly, a significant relationship was also found between age and type of anesthesia during the 6 hour and 24 hour postoperative periods respectively.Conclusions: The study revealed that most patients reported experiencing anxiety before surgery, and a connection was identified between this preoperative anxiety and the level of pain experienced after the operation. It showed that preoperative anxiety had a significant relationship in the immediate postoperative period. Further dimensions like preoperative medications, postoperative medications and care could be added to make the study more effective.